Work engagement, emotional exhaustion, and OCB-civic virtue among nurses: a multilevel analysis of emotional supervisor support - Pohl, Sabine; Djediat, Abdel; Van der Linden, Jan; Closon, Caroline; Galletta, Maura (Frontiers in Psychology, 2023)
Introduction This study investigates the moderating role of supervisor emotional support at the group level on the relationship between emotional exhaustion and work engagement with organizational citizenship behavior-civic virtue (OCB-civic virtue) at the individual level among nurses. Method A cross-sectional study was carried out on 558 nurses nested in 36 working units from two hospitals in Algiers. A multilevel analysis using Hierarchical Linear Modeling was performed. Results Results show that the positive effect of work engagement on OCB-civic virtue was moderated by supervisor emotional support at group level. The nurses emotional exhaustion and OCB-civic virtue negative relationship at the individual level is buffered by supervisor emotional support at group level. Discussion In consequence, supervisor emotional support experienced by the team has an influence on the emotional exhaustion and work engagement OCB-civic virtue relationship.